THE STAGES OF OF TECTONIC-MAGMATIC ACTIVIZATION IN THE HISTORY OF EASTERN PRYAZOVYAN BLOK OF THE UKRAINIAN SHIELD - KISELYOV, V.; BORODYNYA, B.; KOZAR, N.; STREKOZOV, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The East Pryazovyan block of Ukrainian Shield after neoarchean cratonization undergone, at least, two stages of tectonomagmatic activization: paleoproterozoic and mesoproterozoic. The development each stages got involved with certain structures (zones) and were accompanied the various magmatism (core magmatism at paleoproterozoic zone of activization and mantle-core magmatism at mesoproterozoic zone). The brief descriptions of ultrametamorphic and magmatic rocks of East Pryazovya and their evolution wrote this paper. Within East Pryazovyan block of Ukrainian shield was determined the Telman zone of tectonomagmatic activization which have northeasterwards strike This zone controls the intrusions of gabbro-piroxenit and picrite-esexite-latite-trachyte subformations. In the making the intrusive bodies took place hydrothermal-metasomatic processes which caused tungsten-molybdenum and polymetallic mineralization. Presented material let us, at new point of viewing, estimated prospect the expansion of source of raw materials of East Pryazovya.